SDHA Germline Variants in Adult Patients With SDHA-Mutant Gastrointestinal Stromal Tumor - Pantaleo, Maria A.; Urbini, Milena; Schipani, Angela; Nannini, Margherita; Indio, Valentina; De Leo, Antonio; Vincenzi, Bruno; Brunello, Antonella; Grignani, Giovanni; Casagrande, Mariaelena; Fumagalli, Elena; Conca, Elena; et al. (Frontiers in Oncology, 2022)
Background: SDH-deficient gastrointestinal stromal tumors (GIST) account for 20-40% of all KIT/PDGFRA-negative GIST and are due to mutations in one of the four SDH-complex subunits, with SDHA mutations as the most frequent. Here we sought to evaluate the presence and prevalence of SDHA variants in the germline lineage in a population of SDHA-deficient GIST. Methods: Germline SDHA status was assessed by Sanger sequencing on a series of fourteen patients with gastric SDHA-deficient GIST. Results: All patients carried a germline SDHA pathogenic variant, ranging from truncating, missense or splicing variants. The second hit was the loss of the wild-type allele or an additional somatic mutation. One third of the patients were over 50 years old. GIST was the only disease presentation in all cases except one, with no personal or familial cancer history. Seven metastatic cases received a multimodal treatment integrating surgery, loco-regional and medical therapy. The mean follow-up time was of ten years, confirming the indolent clinical course of the disease. Conclusion: SDHA germline variants are highly frequent in SDHA-deficient GIST and the disease may occur also in older adulthood. Genetic testing and surveillance of SDHA-mutation carriers and relatives should be performed.